2018
DOI: 10.4103/joc.joc_2_18
|View full text |Cite
|
Sign up to set email alerts
|

Correlative study of cytological features in grading of invasive breast carcinoma

Abstract: Context:Fine-needle aspiration cytology (FNAC) is a proven diagnostic technique for establishing the benign or malignant character of breast lesions. Several cytological grading systems have been proposed for grading of carcinoma breast, with results similar to histologic grades.Aims:This study sought to evaluate the prognostic value of FNAC in invasive ductal carcinoma of breast by correlating it with histological grade.Settings and Design:Tertiary care hospital, retrospective analytical study.Patients and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…A statistically significant correlation between the cytological and histological grade with a Spearman correlation coefficient r= 0.831 and P value of <0.001. Similar to studies done by Sinha A et al [3] (r=0.97, p <0.01) and Pal S et al [19] (r=0.804, p-0.000).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A statistically significant correlation between the cytological and histological grade with a Spearman correlation coefficient r= 0.831 and P value of <0.001. Similar to studies done by Sinha A et al [3] (r=0.97, p <0.01) and Pal S et al [19] (r=0.804, p-0.000).…”
Section: Discussionsupporting
confidence: 90%
“…Fine-needle aspiration cytology (FNAC) which is widely used for the diagnosis of breast malignancies before planned surgery, is used only to differentiate benign from malignant and the morphology of tumour. [3] The assessment of grading in cytology allows assessment of the tumor in situ which facilitates in deciding the most suitable treatment. Also, overtreatment of low-grade tumors can be avoided hence reduces the post treatment morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reported study showed a statically significant association between cytologic and histologic grades (r=0.97; p<0.01) with sensitivity and specificity 100% and 93.95% respectively. [7] In another series of cases studied also showed good correlation of cytology and histopathological grading and substantial kappa value of agreement i.e. k=0.737 [8] .…”
Section: Discussionmentioning
confidence: 69%
“…Data from surgical specimens were included in the study according to Pathological staging based on recommendations from AJCC 2018 (edition VIII) for TNM classification [ 14 ] and according to the Nottingham Histologic Score system [ 15 ].…”
Section: Methodsmentioning
confidence: 99%